Cooking innovations [ using hydrocolloids for thickening, gelling and emulsification - Nussinovitch, A.; Hirashima, Madoka (CRC Press, 2014)
"Hydrocolloids are among the most commonly used ingredients in the food industry. They function as thickeners, gelling agents, texturizers, stabilizers, and emulsifiers. They also have applications in the areas of edible coatings and flavor release. Thanks to molecular gastronomy, they have now been brought to the forefront of modern cuisine -- available in small quantities for everyday use. While there a number of books devoted to production scale use of hydrocolloids, no book has yet addressed the needs of the chef. This volume is fully devoted to the fascinating topic of hydrocolloids and their unique applications in the kitchen.Each chapter addresses a particular hydrocolloid, protein hydrocolloid, or protein-polysaccharide complex. Starting with a brief description of the chemical and physical nature of the item, the authors go on to explore its manufacture and biological/toxicological properties. Emphasizing practical information for the professional chef and amateur cook alike, each chapter includes recipes demonstrating that particular product?s unique abilities in cooking. Several formulations have been chosen specifically for food technologists, who will be able to manipulate the product for large-scale use or as a starting point for novel industrial formulations. "-- Provided by publisher